Antithymocyte Globulin Induction Dosed on Ideal Body Weight: Absolute Lymphocyte Count (ALC) Depletion in Kidney Transplant Recipients with and without Obesity - Richard Ramos; Scott T. Benken; Jamie J. Benken (Clinical Transplantation, 2026)
ABSTRACT Objective This study evaluated weight‐based dosing of antithymocyte globulin, or ATG, using ideal body weight (IBW) in kidney transplant patients with and without obesity. Methods This was a single‐center, retrospective cohort study of adult kidney transplant recipients who received ATG for induction from 8/2022 to 8/2023. Patients were divided into groups based on obesity status (i.e., body mass index [BMI] ≥ 30). The primary comparative endpoint was the average absolute lymphocyte count (ALC) across post‐operative days (POD) 1 through 4. Secondary comparative endpoints included total ATG dose, hematologic outcomes, graft function, infection, rejection, malignancy, graft survival, and overall survival. Continuous data was assessed for normality, then compared using either the Student t‐test or the Mann‐Whitney U test and presented as averages ± standard deviation or median (interquartile range). Categorical data were compared using the chi‐square or Fisherʼs exact test and presented as counts (%). An a priori power calculation demonstrated that 126 patients (63 per group) were required to detect a 0.1 k/uL difference between groups with alpha = 0.05 and 80% power. Results Baseline characteristics were similar between groups; however, the group with obesity had more Black patients and fewer Hispanic and Asian/Pacific Islander patients. Patients with obesity more frequently had HTN and DM as their ESRD etiologies and experienced more delayed graft function. En bloc transplants were more common in the group without obesity. The average ALC POD1‐4 was similar across groups. The total ATG dose, expressed as mg/kg IBW, was the same between groups. The total ATG dose, expressed as mg/kg actual body weight (ABW), was significantly lower in the obese group. In the group with obesity, the average WBC count POD1‐ 4 was higher, eGFR was lower, and the incidence of CMV viremia was higher. Rejection rate, graft survival, and patient survival were similar between groups. Conclusions Dosing ATG based on IBW results in similar ALC depletion in patients with and without obesity. There were similar allograft and safety findings observed between groups. Compared with theoretical ABW dosing, this IBW dosing strategy resulted in significantly less ATG use, potentially leading to substantial cost savings.